2019 IEEE/ACM 5th International Workshop on Data Analysis and Reduction for Big Scientific Data (DRBSD-5) 2019
DOI: 10.1109/drbsd-549595.2019.00012
|View full text |Cite
|
Sign up to set email alerts
|

Using Machine Learning to Reduce Ensembles of Geological Models for Oil and Gas Exploration

Abstract: Exploration using borehole drilling is a key activity in determining the most appropriate locations for the petroleum industry to develop oil fields. However, estimating the amount of Oil In Place (OIP) relies on computing with a very significant number of geological models, which, due to the ever increasing capability to capture and refine data, is becoming infeasible. As such, data reduction techniques are required to reduce this set down to a smaller, yet still fully representative ensemble. In this paper w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The application of Random Forest in petroleum exploration has been gaining traction in recent years. For instance, Roubícková et al [48] utilized Random Forest to reduce ensembles of geological models for oil and gas exploration. They found that the Random Forest algorithm effectively identifies the critical grouping of models based on the most essential feature.…”
Section: Random Forestmentioning
confidence: 99%
“…The application of Random Forest in petroleum exploration has been gaining traction in recent years. For instance, Roubícková et al [48] utilized Random Forest to reduce ensembles of geological models for oil and gas exploration. They found that the Random Forest algorithm effectively identifies the critical grouping of models based on the most essential feature.…”
Section: Random Forestmentioning
confidence: 99%
“…Examples of machine learning utilization are petroleum exploration and production forecasting [53], [59], detection and correction of equipment malfunctions [72], maintenance support system [33], reservoir modeling and characterization [21], [31] and drilling performance optimization [30], [63].…”
Section: Machine Learning In Oil and Gasmentioning
confidence: 99%
“…In determining locations to develop oil fields takes significant effort to manually process and interpret well log data [60]. Many machine learning-driven approaches have been proposed to address the lengthy and time-consuming issue [10], [32], [53], [60]. However, none had succeeded in a fully automated process without human intervention in interpreting and concluding the results [10], [53], [60].…”
Section: Machine Learning In Oil and Gasmentioning
confidence: 99%
See 2 more Smart Citations